Outbreaks of human trichinellosis caused by consumption of dog meat in China - Cui J.; Wang Z.Q. (Parasite, 2001)
Dog meat has become an important source of Trichinella infection for humans in China. The first documented outbreak of human trichinellosis resulting from the consumption of dog meat occurred in China in 1974. Until 1999, the outbreaks with this source of infection occurred mostly in Northeast of China (81 cases in five outbreaks in Jilin and two in Liaoning), Beijing (six cases) and Henan provinces (two cases). The epidemiological surveys were performed in nine Provinces or Autonomous Regions of China among 19,662 dogs samples. Dogs trichinellosis prevalence ranged from 7 % in Henan to 39.5 % in Heilongjiang, with an overall prevalence of 21.1 %. Based on random amplified polymorphic DNA fingerprint (RAPD), some dog isolates of Heilonjiang and Jilin provinces were recently identified as Trichinella nativa, suggesting that this parasite is widely distributed among dogs in Northeast of China, while Trichinella spiralis in swine appears to be a common parasite throughout China. Since the Trichinella larvae in dog meat is resistant to freezing, caution should be paid to the consumption of dog meat even if it had been frozen.